In our backyard : - Wagner, Travis (John Wiley & Sons, Inc, 1993)
Most attempts to control pollution have been piecemeal, focusing on one environmental component at a time, such as air or water, and have not addressed the big picture. Such efforts have not fully accounted for the Earth's fundamental interconnectedness and unity; as a result, pollution control has often lagged behind pollution-related problems. This book puts all the pieces together as it explains how pollution affects all components of the environment. Using layperson's language and an easy-to-use question and answer format, it describes: how the components of the environment operate together; major sources of pollution; and what we can do to clean up our surface water, groundwater, and air. Care has been taken to avoid bias and to present only the most sound, objective data available.